Genetic Effects Conferring Heat Tolerance in a Cross of Tolerant × Susceptible Maize (Zea mays L.) Genotypes - Naveed, Muhammad; Ahsan, Muhammad; Akram, Hafiz M.; Aslam, Muhammad; Ahmed, Nisar (Frontiers in Plant Science, 2016)
Incessant rise in ambient temperature is threatening sustainability of maize productions, worldwide. Breeding heat resilient synthetics/hybrids is the most economical tool while lack of knowledge of gene action controlling heat and yield relevant traits in maize is hampering progress in this regard. The current study, therefore, was conducted using analyses of generation mean and variance, and narrow sense heritability (h2n) and genetic advance as percent of mean (GAM%). Initially, one hundred inbred lines were evaluated for cell membrane thermo-stability and grain yield per plant on mean day/night temperatures of 36.6°C/22.1°C in non-stressed (NS) and 42.7°C/25.7°C in heat-stressed (HS) conditions. From these, one tolerant (ZL-11271) and one susceptible (R-2304-2) genotypes were crossed to develop six basic generations, being evaluated on mean day/night temperatures of 36.1°C/22.8°C (NS) and 42.3°C/25.9°C (HS) in factorial randomized complete block design with three replications. Non-allelic additive-dominance genetic effects were recorded for most traits in both conditions except transpiration rate, being controlled by additive epistatic effects in NS regime. Dissection of genetic variance into additive (D), dominance (H), environment (E) and interaction (F) components revealed significance of only DE variances in HS condition than DE, DFE and DHE variances in NS regime which hinted at the potential role of environments in breeding maize for high temperature tolerance. Additive variance was high for majority of traits in both environments except ear length in NS condition where dominance was at large. Higher magnitudes of σ2D, h2n and GAM% for cell membrane thermo-stability, transpiration rate, leaf firing, ear length, kernels per ear and grain yield per plant in both regimes implied that simple selections might be sufficient for further improvement of these traits. Low-to-moderate GAM% for leaf temperature and 100-grain weight in both conditions revealed greater influence of genotype-environment interactions, indicating ineffective direct selection and advocating for further progeny testing. In conclusion, pyramiding of heritable genes imparting heat tolerance in maize is achievable through any conventional breeding strategy and generating plant material with lowest cellular injury and leaf firing, and higher transpiration rate, ear length, kernels per ear and grain yield per plant.